MASTURBASI DAN GUILTY FEELING PADA REMAJA - Niman, Susanti; Budi Arianto, Albertus; Shinta Parulian, Tina; Saputra, Aloysius Hendra (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
The development of reproductive organs and hormones triggers changes in sexual behavior in adolescents. Masturbation is a sexual behavior that often occurs in adolescents. Masturbation has a negative stigma because it is taboo to do. Feelings of guilt can be experienced by teenagers who masturbate. This study aims to determine the correlation of masturbation with feelings of guilt in adolescents. The research method is a cross-sectional correlation. The research sample used convenience sampling and collected as many as 385 respondents. The instruments used are masturbation behavior and feelings of guilt. Data analysis was performed using the Kendall-Tau correlation test. The study's results showed that 72.2% of respondents were male and 27.8% female. The average age of the respondents was 17.06 years, the moderate guilty feeling was 9.50, and the average masturbation behavior was 54.99. There is a negative correlation between masturbation behavior and guilty feelings (p-value 0.001; r = -0.124). In conclusion, there is a correlation between masturbation behavior and guilty feeling. The more masturbation behavior that is done, the less sense of guilt will be increasingly not felt. Sexual behavior involves not only biological aspects but psychological, social and moral aspects. Teenagers need to get health education about healthy sexual behavior.